Inhibition of HSP90 and Activation of HSF1 Diminish Macrophage NLRP3 Inflammasome Activity in Alcohol‐Associated Liver Injury - Choudhury, Asmita; Bullock, Daniel; Lim, Arlene; Argemi, Josepmaria; Orning, Pontus; Lien, Egil; Bataller, Ramon; Mandrekar, Pranoti (Alcoholism, clinical and experimental research, 2020)
Background Activation of NLRP3 in liver macrophages contributes to alcohol‐associated liver disease (ALD). Molecular chaperone heat shock protein (HSP) 90 facilitates NLRP3 inflammasome activity during infections and inflammatory diseases. We previously reported that HSP90 is induced in ALD and regulates proinflammatory cytokines, tumor necrosis factor alpha, and IL‐6. Whether HSP90 affects IL‐1β and IL‐18 regulated by NLRP3 inflammasome in ALD is unknown. Here, we hypothesize that HSP90 modulated NLRP3 inflammasome activity and affects IL‐1β and IL‐18 secretion in ALD. Methods The expression of HSP90AA1 and NLRP3 inflammasome genes was evaluated in human alcoholic livers and in mouse model of ALD. The importance of HSP90 on NLRP3 inflammasome activation in ALD was evaluated by administering HSP90 inhibitor, 17‐dimethylaminoethylamino‐17‐demethoxygeldanamycin (17‐DMAG) to mice subjected to ALD, and in vitro to bone marrow‐derived macrophages (BMDM) stimulated with LPS and ATP. The effect of activation of HSF1/HSPA1A axis during HSP90 inhibition or direct activation during heat shock of BMDMs on NLRP3 activity and secretion of downstream cytokines was evaluated. Results We found positive correlation between induction of HSP90 and NLRP3 inflammasome genes in human alcoholic cirrhotic livers. Administration of 17‐DMAG in mouse model of ALD significantly down‐regulated NLRP3 inflammasome‐mediated caspase‐1 (CASP‐1) activity and cytokine secretion, with reduction in ALD. 17‐DMAG‐mediated decrease in NLRP3 was restricted to liver macrophages. Using BMDMs, we show that inhibition of HSP90 prevented CASP‐1 activity, and Gasdermin D (GSDMD) cleavage, important in release of active IL‐1β and IL‐18. Interestingly, activation of the heat shock factor 1 (HSF1)/HSPA1A axis, either during HSP90 inhibition or by heat shock, decreased NLRP3 inflammasome activity and reduced secretion of cytokines. Conclusion Our studies indicate that inhibition of HSP90 and activation of HSF1/HSPA1A reduce IL‐1β and IL‐18 via decrease in NLRP3/CASP‐1 and GSDMD activity in ALD.